Modified supracondylar dome osteotomy: our experience in 11 children - ., Abhinav; Manav, Ajoy Kumar; Singh, Arjun (International Journal of Research in Orthopaedics, 2017)
Background: The present retrospective study was done with 11 children having cubitus varus following supracondylar fractures to access the stability of modified domeosteotomy and its fixation with k-wires in older children. Methods: 11 children, 7 males & 4 females were included in the study. The osteotomy was performed through posterior approach. The triangular wedge rotated inside the notch was inherently stable and also fixed with k-wires. Patients were followed at regular intervals. K wires were removed at 6 weeks and the physiotherapy started. Results: The correction obtained under vision was well maintained post operatively in 10 out of 11 cases. In only one case there was back out of k-wires and loss of correction. 5 cases had excellent result followed by 4 good and one fair result. Conclusions: Modified dome osteotomy performed through posterior approach and fixed with k-wires gives good results. Removal of the k-wires is simple. However, in children above 14 years plate fixation might be better to prevent loss of correction.